Use of Nicotiana tobaccum extractions as a molluscicide to the snail of Bulinus truncates - Baghdad Science Journal (مجلة بغداد للعلوم, 2009)
Nicotiana tobaccum L (Solanacea) extracts are used as a mollusciede to the snail Bulinus truncatus the intermediate host of urinary Schistosomiasis. LC50 of the extracts to the snail with 24 hour was 3.27 ml/l? 48 hour was 3.33 ml/l? 72 hour was 2.67 ml/l and 96 hour was 2.28ml/l. This study showed the ability to use the leaf extracts in the control of this type of snail.